Disruption of β-catenin/CBP signaling inhibits human airway epithelial–mesenchymal transition and repair. (November 2015) - Moheimani, Fatemeh; Roth, Hollis M.; Cross, Jennifer; Reid, Andrew T.; Shaheen, Furquan; Warner, Stephanie M.; Hirota, Jeremy A.; Kicic, Anthony; Hallstrand, Teal S.; Kahn, Michael; Stick, Stephen M.; Hansbro, Philip M.; et al.
Abstract: The epithelium of asthmatics is characterized by reduced expression of E-cadherin and increased expression of the basal cell markers ck-5 and p63 that is indicative of a relatively undifferentiated repairing epithelium. This phenotype correlates with increased proliferation, compromised wound healing and an enhanced capacity to undergo epithelial–mesenchymal transition (EMT). The transcription factor β-catenin plays a vital role in epithelial cell differentiation and regeneration, depending on the co-factor recruited. Transcriptional programs driven by the β-catenin/CBP axis are critical for maintaining an undifferentiated and proliferative state, whereas the β-catenin/p300 axis is associated with cell differentiation. We hypothesized that disrupting the β-catenin/CBP signaling axis would promote epithelial differentiation and inhibit EMT. We treated monolayer cultures of human airway epithelial cells with TGFβ1 in the presence or absence of the selective small molecule ICG-001 to inhibit β-catenin/CBP signaling. We used western blots to assess expression of an EMT signature, CBP, p300, β-catenin, fibronectin and ITGβ1 and scratch wound assays to assess epithelial cell migration. Snai-1 and -2 expressions were determined using q-PCR. Exposure to TGFβ1 induced EMT, characterized by reduced E-cadherin expression with increased expression of α-smooth muscle actin and EDA-fibronectin. Either co-treatment or therapeutic administration of ICG-001 completely inhibited TGFβ1-induced EMT. ICG-001 also reduced the expression of ck-5 and -19 independent of TGFβ1. Exposure to ICG-001 significantly inhibited epithelial cell proliferation and migration, coincident with a down regulation of ITGβ1 and fibronectin expression. These data support our hypothesis that modulating the β-catenin/CBP signaling axis plays a key role in epithelial plasticity and function.